2019
DOI: 10.1038/s41598-019-51855-w
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular adenosine triphosphate is associated with airflow limitation severity and symptoms burden in patients with chronic obstructive pulmonary disease

Abstract: Extracellular adenosine triphosphate (eATP)-driven inflammation was observed in chronic obstructive pulmonary disease (COPD) but was not investigated in patients’ blood. Therefore, this study aimed to investigate eATP concentration in plasma of COPD patients and its association with disease severity and smoking. Study included 137 patients with stable COPD and 95 control subjects. eATP concentration was determined in EDTA plasma by luminometric method, and mRNA expression of eATP receptors P2X7R and P2Y2R was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…For calculation of multicomponent indices related to COPD assessment, the following data were collected for COPD patients: body mass index (BMI), score obtained from modified Medical Research Council (mMRC) Dyspnea Scale, number of previous exacerbations and Charlson’s comorbidity index. Afterwards, BODCAT (BMI, airflow obstruction, dyspnea, CAT score), BODEx (BMI, airflow obstruction, dyspnea, previous exacerbations), CODEx (Charlson’s comorbidity index, airflow obstruction, dyspnea, previous exacerbations) and DOSE (dyspnea, airflow obstruction, smoking status, previous exacerbations) were calculated [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For calculation of multicomponent indices related to COPD assessment, the following data were collected for COPD patients: body mass index (BMI), score obtained from modified Medical Research Council (mMRC) Dyspnea Scale, number of previous exacerbations and Charlson’s comorbidity index. Afterwards, BODCAT (BMI, airflow obstruction, dyspnea, CAT score), BODEx (BMI, airflow obstruction, dyspnea, previous exacerbations), CODEx (Charlson’s comorbidity index, airflow obstruction, dyspnea, previous exacerbations) and DOSE (dyspnea, airflow obstruction, smoking status, previous exacerbations) were calculated [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Airflow limitation was diagnosed by spirometry on a Master-Screen Pneumospirometer (Jaeger, Wurzburg, Germany), and airflow obstruction was confirmed if FEV 1 /FVC was lower than 0.70 after three acceptable measurements. Furthermore, diffusing capacity for carbon monoxide (DLCO) was measured three times on a Master-Screen PFT Pro (Jaeger, Wurzburg, Germany), as described before [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among them, in 16% of COPD patients inflammation was persistent, and associated with mortality and exacerbations [21]. From our previous studies, we observed that our COPD cohort might also show characteristics of systemic inflammation because of increased concentrations of CRP and Fbg [22] that are being common inflammatory parameters as well as extracellular adenosine triphosphate (eATP) [23] and extracellular heat shock protein 70 (eHsp70) [24] which act like damage-associated molecular patterns (DAMPs). In addition, a previous investigation showed that there were significant associations between the aforementioned parameters with lung function and disease severity, as well as symptoms severity and history of exacerbations, and different multicomponent clinical parameters used for the assessment of dyspnoea, exacerbations and lung impairment.…”
Section: Introductionmentioning
confidence: 96%
“…For calculation of multicomponent indices related to COPD assessment, following data were collected for COPD patients: body mass index (BMI), score obtained from modi ed Medical Research Council (mMRC) Dyspnoea Scale, number of previous exacerbations and Charlson's comorbidity index. Afterwards, BODCAT (BMI, air ow obstruction, dyspnoea, CAT score), BODEx (BMI, air ow obstruction, dyspnoea, previous exacerbations), CODEx (Charlson's comorbidity index, air ow obstruction, dyspnoea, previous exacerbations) and DOSE (dyspnoea, air ow obstruction, smoking status, previous exacerbations) were calculated (29).…”
Section: Participantsmentioning
confidence: 99%
“…Air ow limitation was diagnosed by spirometry on a Master-Screen Pneumo spirometer (Jaeger, Germany), and air ow obstruction was con rmed if FEV 1 /FVC was lower than 0.70 after three acceptable measurements. Furthermore, diffusing capacity for carbon monoxide (DLCO) was measured three times on Master-Screen PFT Pro (Jaeger, Wurzburg, Germany), as described before (29).…”
Section: Assessment Of Lung Functionmentioning
confidence: 99%